Magnetic recovery reveals sequential extraction bias and supports mass-conservative assessment of lanthanum-based sediment phosphorus inactivation - Zhe Wang; Liling Wang; Chengyan Bao; Enyang Liu; Xinnuo Liu; Zezhen Pan; Feijian Mao; Xingxing Wang; Jiake Li; Deyi Wu; Qiang Xie; Zimeng Wang (Water Research, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Preparation of K2CO3-activated biochar from peanut shell and Chlorella for enhanced carbamazepine adsorption: Performance, mechanism, and reusability - Zhenzhen Li; Jiayu Wu; Ting Cheng; Liling Zhou; Yujia Yang (Journal of Environmental Management, 2026)

Long-term PM2.5 exposure and timing of pubertal development in boys and girls: A prospective cohort study in Chongqing, China - Liling Xie; Jingwei Li; Xizou An; Haiying Zhong; Wenbing Luo; Muhammad Fahad Tahir; Shunqing Luo; Cui Song; Xiaohua Liang (Environmental Research, 2026)

Effects of ultrasound, blanching, and ethanol pretreatments on drying characteristics, microstructure, and quality of apricots using hot air-assisted radio frequency energy - Jiahong Yuan; Dongsheng Hu; Qianjie Xiong; Rui Li; Liling Yang; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2026)

Why is Bacillus cereus group enriched in sufu? -A study on prevalence, characterization and traceability - Zekun Jin; Li Li; Yin Zheng; Peipei An; Liling Lu; Zhaohui Zhou (Food Microbiology, 2026)

Antimony exposure promotes cardiac fibrosis via lactate-mediated cardiomyocyte-fibroblast crosstalk: A novel Sirt1-glycolysis axis - Xin Li; Zhenzhen Dai; Xiaoyong Ren; Hao Zhao; Lirong Chan; Ruotong Wu; Xinyi Xiao; Qiao Liu; Liling Su (Journal of Environmental Sciences, 2026)

A multi-dimensional modified deep learning framework for predicting potential creep-type landslides based on geological data - Yue Liu; Peihua Xu; Chen Cao; Liling Jin; Bo Han; Rongchen Ma; Chensi Li (Earth Science Informatics, 2026)

Concurrent biodegradation of tylosin and tilmicosin by a novel Paracoccus versutus 4-B-2 - Zhengyan Chen; Anqi Liu; Junzhe Cui; Chunhui Liu; Huijuan Li; Ziyi Quan; Yaxu Liu; Xiao Guo; Xiaoyu Wang; Liling Fan; Bo Wang (Journal of Hazardous Materials, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Towards low-carbon zinc extraction from zinc-containing electric arc furnace dust: A review of pyrometallurgical and hydrometallurgical routes - Yuqian Liu; Haichuan Li; Liling Jin; Dongdong Zhou; Shiyuan Liu (Journal of Environmental Chemical Engineering, 2026)

Increasingly frequent compound climate events worsen economic disparities in China's urban agglomerations - Chao He; Liling Chu; Yiqi Zhou; Yanwen Wang; Yilin Li; Qixin Hu; Song Hong; Chunping Miao (Urban Climate, 2026)

Biomass organohydrogel toward green wearable sensors: Enhancing high and low temperature sensing properties, UV shielding properties, and long-term cycling durability - Ruibing Shen; Qiaoyan Wei; Liangdong Ye; Liling Zhang; Yanyou Huang; Yuling Lv; Ziwei Li; Zuocai Zhang; Xiaokun Han; Shaorong Lu (Chemical Engineering Journal, 2026)

Polyurethane grouting materials for infrastructure reinforcement in cold regions: State of the art and perspectives - Tan Liling; Guo Ming; Yu Wenbing; Han Fenglei; Li Guo; Gao Meng (Cold Regions Science and Technology, 2026)

TMC6 Protects Against Ischemic Neuronal Injury by Activating Rap1/Rac1 Signaling to Restore Mitochondrial Dynamics and Mitophagy - Xuemei Quan; Huo Liang; Haiyin Long; Xiawei Wang; Liling Feng; Xia Zhou; Yuan Chen; Yanhua Li; Xiaofeng Li (Molecular Neurobiology, 2026)

Balancing human development and environmental protection: Evidence from the Yangtze River Economic Belt ecological and environmental protection policy - Liling Zhu; Fei Chen; Huiqiang Zhang; Yi Li (Journal of Cleaner Production, 2025)

Assessment of potentially toxic elements (PTEs) in surface and groundwater of volcanic and granite regions of Hainan Island, China: Pollution status, sources, and health risk evaluation - Jianzhou Yang; Yong Li; Shengyue Liang; Min Zhang; Jingjing Gong; Yufang Li; Qiankun Yan; Xiaohui Sun; Zuyang Xu; Xueju Liu; Shuqi Hu; Jianweng Gao; et al. (Environmental Geochemistry and Health, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Effect of salt valence and ionic strength on the rheology and 3D printing performance of walnut protein emulsion gels - Guohua Li; Bo Wang; Liling Yang; Weiqiao Lv; Hongwei Xiao (Food Hydrocolloids, 2025)

Unraveling microbial assembly and co-occurrence relationship at seasonal and vertical scales in an aged organic-contaminated site - Zhirui Qin; Zhenhua Zhao; Liling Xia; Jiayuan Liu; Xuan Li; Aiwei Zhang; Yue Wang; Jingwei Wang (International Biodeterioration & Biodegradation, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

Effects of innovative dry-blanching on moisture, cell wall structure, physicochemical properties and volatile compounds of microwave infrared coupled dried ginger (Zingiber officinale roscoe) - Shiyu Zeng; Bingzheng Li; Liling Yang; Weiqiao Lv; Hongwei Xiao (Food Chemistry, 2025)

A multiplex RT‑PCR detection system for pepper co-infection by three potyviruses - Tiyuan Xia; Liling Mo; Xinyang Chen; Wang Wang; Pengyu Liu; Xingmei Tao; Xuan Yi; Zuqin Qiao; Yongfu Zhang; Xiaoqin Li (Journal of General Plant Pathology, 2025)

Innovation-driven cities: Reconciling economic growth and ecological sustainability - Fei Chen; Liling Zhu; Huiqiang Zhang; Yi Li (Sustainable Cities and Society, 2025)

Climate change and human activities drive the warm-season rooftop solar photovoltaic potential in the Chinese Chengdu-Chongqing urban agglomeration - Yilin Li; Lijun Liu; Tianyu Zhang; Youjia Liang; Zhenghong Chen; Liling Chu; Chao He (Sustainable Cities and Society, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

Revealing the active ingredients and mechanisms of Xiatianwu against hepatocellular carcinoma: a study based on network pharmacology and bioinformatics - Hui Wang; Weina Zhang; Liling Li; Hong Wang; Honglin Jiang; Wenna Li; Jinchang Huang; Yuxiang Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comparative lipidomics analysis of seed oils from nine tropical fruits: Emphasizing the fatty acid and lipid molecule profiles - Jingtao Cui; Tong Li; Yanchi Zhou; Liling Wang; Tian Li; Weimin Zhang (Food Research International, 2024)

Lactococcus lactis subsp. lactis LJL7m20 strongly inhibits growth of the Bacillus cereus group from sufu - Jialu Xian; Huifang Wang; Siying Diao; Nan Zhang; Sisi Lin; Rui Zhang; Zekun Jin; Zhaohui Zhou; Liling Lu; Sameh A. Korma; Li Li (Food Bioscience, 2024)

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Unveiling the dynamics of dry-and-humid, day-and-night, and compound heat waves across 209 Cities in China during 1974–2021 - Lijun Liu; Liling Chu; Youjia Liang; Jiangang Li; Miao Yu; Chao He (Urban Climate, 2024)

Effect of κ-carrageenan on physicochemical and 3D printing properties of walnut protein-stabilized emulsion gel - Guohua Li; Bo Wang; Weiqiao Lv; Liling Yang; Hongwei Xiao (Food Hydrocolloids, 2024)

Allicin Ameliorated High-glucose Peritoneal Dialysis Solution-induced Peritoneal Fibrosis in Rats via the JAK2/STAT3 Signaling Pathway - Linwang Gan; Lei Geng; Qiancheng Li; Liling Zhang; Yan Huang; Jiaru Lin; Santao Ou (Cell Biochemistry and Biophysics, 2024)

Polystyrene microplastics trigger testosterone decline via GPX1 - Jiayuan Qu; Liling Wu; Li Mou; Changjiang Liu (Science of The Total Environment, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Protective Effect of CXCR7 Against Hypoxia/Reoxygenation Injury in Renal Tubular Epithelial Cells - Ping Meng; Chunli Liu; Jingchun Li; Ping Fang; Liling Chen (Cell Biochemistry and Biophysics, 2024)
Acute kidney injury (AKI) is a multifactorial syndrome with complex pathophysiology and prognosis. Ischaemia‒reperfusion injury (IRI) is a major cause of induced AKI. The aim of this study was to investigate the effect of upregulated CXCR7 expression on renal tubular epithelial cell apoptosis induced by hypoxia/reoxygenation (H/R). HK-2 cells were divided into three groups: control group (pcDNA3.1), hypoxia/reoxygenation + pcDNA3.1 group (H/R+pcDNA3.1) and CXCR7 overexpression + hypoxia/reoxygenation group (H/R+ Flag-CXCR7). Protein levels of renal tubular epithelial cell injury-, apoptosis- and autophagy-related markers were assessed by qRT‒PCR, Western blotting, flow cytometry (FCM), immunofluorescence and transmission electron microscopy (TEM). In addition, HK-2 cells were treated with the autophagy inhibitor 3-MA and divided into 3 groups: control group, 3-MA + pcDNA3.1 group, and 3-MA + Flag-CXCR7 group. Changes in autophagy and apoptosis in renal tubule epithelial cells were assessed by Western blotting and FCM. Compared with those in the control group, the protein and mRNA expression levels of CXCR7 in HK-2 cells were significantly lower under H/R conditions. Under H/R conditions, CXCR7 overexpression in HK-2 cells significantly downregulated the expression of NGAL. Moreover, CXCR7 overexpression significantly decreased H/R-induced cleaved PARP-1 and cleaved Caspase 3 levels, increased the level of the antiapoptotic protein BCL-2 and the autophagy-related molecules ATG5 and LC3B II, and significantly inhibited the expression of P62. Autophagy flow and TEM also showed that CXCR7 significantly promoted autophagy. CXCR7 significantly alleviated the 3-MA-induced inhibition of autophagy and increase in apoptosis. Upregulated CXCR7 expression can inhibit renal tubular epithelial cell apoptosis and damage by regulating autophagy. In conclusion, CXCR7 is a promising target for the prevention and/or treatment of AKI.

First report of chilli veinal mottle virus infecting Lactuca sativa in China - Yue Chen; Gui Gao; Ting Ting Li; Jie Chen; Yue Yan Yin; Jing Zhong; Liling Zhao; Yi Cao; Ming Ding (Journal of Plant Pathology, 2024)

Glutamicibacter nicotianae AT6: A new strain for the efficient biodegradation of tilmicosin - Huijuan Li; Hao Zhou; Liling Fan; Long Meng; Yanyun Zhao; Lanmei Zhao; Bo Wang (Journal of Environmental Sciences, 2024)

First report of pod pepper vein yellows virus infecting Solanum nigrum L. in China - Yongfu Zhang; Pengyu Liu; Liling Mo; Xinyang Chen; Wang Wang; Xingmei Tao; Xiaoqin Li (Journal of Plant Pathology, 2024)

NLRC3 attenuates osteoclastogenesis by limiting TNFα+ Th17 cell response in osteoporosis - Lingyan Ren; Guangjun Liu; Yun Bai; Liling Gu; Yuan Wang; Li Sun (Journal of Molecular Medicine, 2024)
NOD-like receptor family CARD domain containing 3 (NLRC3) is the intracellular protein belonging to NLR (NOD-like receptor) family. NLRC3 can negatively regulate inflammatory signal transduction pathways within the adaptive and innate immunocytes. However, studies need to elucidate the biological role of NLRC3 in bone remodeling. Herein, our study proved that NLRC3 prevents bone loss by inhibiting TNFα + Th17 cell responses. In osteoporosis, NLRC3 attenuated TNFα + Th17 cell accumulation in the bone marrow. However, osteoporosis (OP) development was aggravated without affecting bone marrow macrophage (BMM) osteoclastogenesis in NLRC3-deficient ovariectomized (OVX) mice. In this study, we transferred the wild-type and NLRC3 −/− CD4 + cells into Rag1 −/− mice. Consequently, we evidenced the effects of NLRC3 in CD4 + T cells on inhibiting the accumulation of TNFα + Th17 cells, thus restricting bone loss in the OVX mice. Simultaneously, NLRC3 −/− CD4 + T cells promoted the recruitment of osteoclast precursors and inflammatory monocytes into the OVX mouse bone marrow. Mechanism-wise, NLRC3 reduced the secretion of TNFα + Th17 cells of RANKL, MIP1α, and MCP1, depending on the T cells. In addition, NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. Collectively, this study appreciated the effect of NLRC3 on modulating bone mass via adaptive immunity depending on CD4 + cells. According to findings of this study, NLRC3 may be the candidate anti-OP therapeutic target. Key messages NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. NLRC3 may be the candidate anti-OP therapeutic target.

Long-term exposure to fine particulate matter constituents in relation to chronic kidney disease: evidence from a large population-based study in China - Yucen Dai; Jianzhong Yin; Sicheng Li; Jiawei Li; Xinyu Han; Quzong Deji; Ciren Pengcuo; Leilei Liu; Zhimiao Yu; Liling Chen; Linshen Xie; Bing Guo; et al. (Environmental Geochemistry and Health, 2024)

Invigorating active sites for amorphous/crystalline heterophased co-based oxyhydroxide/tungstate toward enhanced electrocatalytic oxygen evolution: Trimetallic codoping-achieved synergistic regulation - Jiejie Feng; Jianting Liu; Changshun Chu; Liling Wei; Huayi Li; Jianquan Shen (Chemical Engineering Journal, 2024)

Multi-omics analysis provides insight into liver metabolism in yellow catfish (Pelteobagrus fulvidraco) under hypoxic stress - Man Wang; Shasha Zhao; Jie Wang; Liling Nie; Li Li; Xiaoming Zhu; Lei Zhang (Aquaculture, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Cobalt-induced apoptosis of cochlear organotypic cultures and HEI-OC1 cells is mediated by Dicer - Xuexin Lin; Liling Li; Jia Luo; Dan Chen; Jingqian Tan; Peng Li (NeuroToxicology, 2024)

Ultrasonic preparation of citral/hydroxypropyl-β-cyclodextrin inclusion complex: Application as a potential antifungal preservative in strawberry storage - Dan Shen; Xia Chang; Liling Zhou; Dandan Hao; Zhongxiang Fang; Yang Shan; Lvhong Huang; Gaoyang Li (Food Control, 2024)

Combined microbe-plant remediation of cadmium in saline-alkali soil assisted by fungal mycelium-derived biochar - Zirun Zhao; Lin Liu; Ying Sun; Liling Xie; Shuo Liu; Mingchun Li; Qilin Yu (Environmental Research, 2024)

Physical, chemical, and rheological properties of konjac glucomannan phosphate ester - Liling Deng; Yongbo Peng; Yan Li; Geng Zhong; Dan Liu; Zhaojing Zhu (Journal of Food Engineering, 2023)

Association Between Wnt Target Genes and Cortical Volumes in Alzheimer’s Disease - Liling Dong; Bo Hou; Caiyan Liu; Chenhui Mao; Xinying Huang; Li Shang; Shanshan Chu; Bin Peng; Liying Cui; Feng Feng; Jing Gao (Journal of Molecular Neuroscience, 2023)
The disproportionate cortical atrophy is an established biomarker for the pathophysiological process of Alzheimer’s disease (AD). However, the genetic basis underlying the cortical atrophy remains poorly defined. Herein, we aim to illustrate the effect of the Wnt target genes on the cortical volumes of AD patients. 82 sporadic AD patients were recruited. All the subjects had history survey, blood biochemical examination, cognitive assessment, MRI morphometry and whole exome sequencing. This report focused on 84 common variants (minor allele frequency > 0.01) of 32 Wnt target genes, including the APC , DAAM1 , DACT1 , DISC1 , LATS2 , TLR2 , WDR61 , and the AXIN , DVL , FZD , LRP , TCF/LEF , WNT family genes. The Wnt target genes showed asymmetric effects on the cortical volumes of AD patients. The right temporal/parietal/occipital cortices were more affected than left temporal/parietal/occipital cortices. Nevertheless, the reverse applied to the frontal cortex. The DACT1 affected the cortical thickness most, followed by the TCF3 and APC . The DACT1 rs698025-GG genotype displayed greater right temporal pole and left medial orbito-frontal gyrus than rs698025-GA genotype (2.4 ± 0.4 vs. 2.0 ± 0.6, P = 0.005; 5.2 ± 0.6 vs. 5.0 ± 0.6, P = 0.001). The brain region most influenced by the Wnt target genes was the right calcarine cortex. In conclusion, the common variants of the Wnt target genes exert asymmetric effects on the cortical volumes of AD patients. The Wnt signaling pathway may play a role in the cortical atrophy of AD patients.

Evaluating the contribution of climate change and urbanization to the reversal in maximum surface wind speed decline: Case study in the Yangtze River Economic Belt, China - Lijun Liu; Youjia Liang; Chao He; Bin Li; Liling Chu; Jiangang Li (Urban Climate, 2023)

Optimizing directional recovery of high-bioavailable phosphorus from human manure: Molecular-level understanding and assessment of application potential - Yao Xu; Nan Li; Libin Yang; Tongcai Liu; Shaoze Xiao; Liling Zhou; Dapeng Li; Jiabin Chen; Yalei Zhang; Xuefei Zhou (Water Research, 2023)

Synergistic effects of carbon cap-and-trade and renewable portfolio standards on renewable energy diffusion - Xiongping Yue; Chao Wang; Boxue Sun; Huanyu Ren; Yong Tan; Liling Huang; Dan Feng; Xin Li (Journal of Cleaner Production, 2023)

Adverse effects of triclosan exposure on health and potential molecular mechanisms - Xuhui Chen; Li Mou; Jiayuan Qu; Liling Wu; Changjiang Liu (Science of The Total Environment, 2023)

NCX2 Regulates Intracellular Calcium Homeostasis and Translocation of HIF-1α into the Nucleus to Inhibit Glioma Invasion - Hongyuan Liu; Ju Yu; Liling Yang; Pengcheng He; Zongping Li (Biochemical Genetics, 2023)
Glioma is the most common tumor of the central nervous system, and its poor prognosis can be linked to hypoxia and gene inactivation. Na + /Ca 2+ exchanger 2 (NCX2) is expressed only in the normal brain and not in other tissues or glioma. We constructed a hypoxic microenvironment to more accurately understand the effect of NCX2 in glioma. Our previous experiments confirmed that NCX2 inhibited the growth of U87 cells in nude mice, indicating that NCX2 is a potential tumor suppressor gene. Malignant tumor cells are often exposed to an anoxic environment. To more accurately understand the effect of NCX2 in glioma, we constructed a hypoxic microenvironment. To detect the localization of NCX2 in transfected U87 cells, immunofluorescence was used. We tested the function of NCX2 in glioma, i.e., how it contributes to the cytosolic Ca 2+ homeostasis by X-Rhod-1. We tested the cell proliferation of NCX2 in glioma in hypoxic using Cell counting kit-8 (CCK8). Cell migration and invasion were evaluated in 24-well transwell matrigel-coated or non-matrigel-coated in hypoxia. NCX2 promoted the proliferation of U87 cells in the hypoxic microenvironment. It inhibited the invasion and migration abilities of U87 cells. We demonstrated that NCX2 was located on the cell membrane and that it reduced intracellular Ca 2+ levels and reactivated P53 and PTEN. We further demonstrated that NCX2 impaired cell invasion through the HIF-1α pathway in glioma. The results indicated that NCX2 plays a key role in glioma formation and tumor invasion functionality.

Nanocellulose-enhanced smart film for the accurate monitoring of shrimp freshness via anthocyanin-induced color changes - Liling Li; Wenxiu Wang; Mengdan Zheng; Jianfeng Sun; Zhizhou Chen; Jie Wang; Qianyun Ma (Carbohydrate Polymers, 2023)

Continued evolution of the Eurasian avian-like H1N1 swine influenza viruses in China - Fei Meng; Yan Chen; Zuchen Song; Qiu Zhong; Yijie Zhang; Chuanling Qiao; Cheng Yan; Huihui Kong; Liling Liu; Chengjun Li; Huanliang Yang; Hualan Chen (Science China Life Sciences, 2023)

Effects of the indoor environment on EEG and thermal comfort assessment in males - Liling Pan; Hanying Zheng; Tingxun Li (Building and Environment, 2023)

Tumor suppressor LHPP suppresses cell proliferation and epithelial-mesenchymal transition in hepatocellular carcinoma cell lines - Lunkun Ma; Huifang Sun; Xichao Xu; Ying Chen; Lu Zhang; Shun Li; Liling Tang (Journal of Physiology and Biochemistry, 2022)

Tumour suppression by Chinese cordyceps extract via antiangiogenic activity - Wenjia Li; Jing Li; Xuefeng Hu; Linghua Xu; Xiaoyu Liu; Zhengming Qian; Liling Jin; Yimin Zhang; Jiangchun Wei; Xingzhong Liu (Mycological Progress, 2022)

Application of the Non-dominated Sorting Genetic Algorithm II in Multi-objective Optimization of Orally Disintegrating Tablet Formulation - Jiaqi Zhang; Yu Yao; Wei Sun; Liling Tang; Xiaodong Li; Huaqing Lin (AAPS PharmSciTech, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

A genome-wide association study reveals that the cytochrome b5 involved in seed reserve mobilization during seed germination in rice - Zhibo Huang; Jifeng Ying; Liling Peng; Shan Sun; Chengwei Huang; Can Li; Zhoufei Wang; Yongqi He (Theoretical and Applied Genetics, 2021)

A Decision-Making Method for Autonomous Collision Avoidance for the Stand-On Vessel Based on Motion Process and COLREGs - Bing Wang; Yixiong He; Weixuan Hu; Junmin Mou; Liling Li; Ke Zhang; Liwen Huang (Journal of Marine Science and Engineering, 2021)
A great number of collision accidents can be attributed to incongruous collision-avoidance actions between the give-way vessel and the stand-on vessel in a crossing or overtaking situation. If the give-way vessel does not take appropriate collision-avoidance action according to international regulations for preventing collisions at sea, the last barrier to pass safely is the appropriate and effective collision-avoidance action taken by the stand-on vessel. To find the proper autonomous collision-avoidance action of the stand-on vessel, a method is proposed that combines quantitative analysis rules of collision-avoidance with the deduction of nonlinear maneuvering motion process based on the mathematical model group, which conformity can reach 90%. This research presents a method to calculate the timing and most effective collision-avoidance actions for the stand-on vessel based on the four-stage theory of encountering vessels and the characteristics of vessel motion. The accuracy of the latest-action timing and the action amplitude for the stand-on vessel can be increased to the level of second and degree, respectively. A novel model of collision risk index is constructed by the latest time of the feasible collision-avoidance action on the precise of different course-altering amplitude. Methods to find the stand-on vessel’s proper collision-avoidance actions in the open sea are presented. The simulation indicates the proposed method for the stand-on vessel can make correct collision-avoidance decisions autonomously.

Phenotype Heterogeneity and Genotype Correlation of MAPT Mutations in a Chinese PUMCH Cohort - Chenhui Mao; Liling Dong; Jie Li; Xinying Huang; Dan Lei; Jie Wang; Shanshan Chu; Caiyan Liu; Bin Peng; Liying Cui; Jing Gao (Journal of Molecular Neuroscience, 2021)

DNAH17 is essential for rat spermatogenesis and fertility - Liling Chen; Jiamin Ouyang; Xueqing Li; Xueshan Xiao; Wenmin Sun; Shiqiang Li; Lin Zhou; Yuandong Liao; Qingjiong Zhang (Journal of Genetics, 2021)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Carbonyl sulfide (COS) and carbon disulfide (CS2) exchange fluxes between cotton fields and the atmosphere in the arid area in Xinjiang, China - Weiwen Jing; Liling Wang; Deqiang Li; Xiaowei Bao; Yingshuang Shi (Environmental Geochemistry and Health, 2019)

Glycosylation and an amino acid insertion in the head of hemagglutinin independently affect the antigenic properties of H5N1 avian influenza viruses - Chunyang Gu; Xianying Zeng; Yangming Song; Yanbing Li; Liling Liu; Yoshihiro Kawaoka; Dongming Zhao; Hualan Chen (Science China Life Sciences, 2019)

Comparison of breast-conserving surgery and mastectomy in early breast cancer using observational data revisited: a propensity score-matched analysis - Kai Chen; Zihao Pan; Liling Zhu; Tingting Hu; Min Peng; Weijuan Jia; Fengxi Su; Shunrong Li; Erwei Song (Science China Life Sciences, 2018)

Two distinct begomoviruses associated with an alphasatellite coinfecting Emilia sonchifolia in Thailand - Liling Zhao; Jing Zhong; Xiaoyun Zhang; Yueyan Yin; Tingting Li; Ming Ding (Archives of Virology, 2018)

Function of quorum sensing and cell signaling in the formation of aerobic granular sludge - Shuo Wang; Wenxin Shi; Tang Tang; Yuying Wang; Liling Zhi; Jinze Lv; Ji Li (Reviews in Environmental Science and Bio/Technology, 2017)

Prefabrication of axially vascularized bone by combining β-tricalciumphosphate, arteriovenous loop, and cell sheet technique - Dongyang Ma; Liling Ren; Zhen Cao; Jianxue Li; Jian Cao; Wenyan Tian; Hong Yao (Tissue Engineering and Regenerative Medicine, 2016)

Fast elimination of malaria by infectious source eradication with artemisinin-based compound - Liling Feng; Xiaoli Luo; Yaofang Zhou; Xingbo Guo; Guoqiao Li (Science China Life Sciences, 2016)

Arsenic Trioxide and Icariin Show Synergistic Anti-leukemic Activity - Zhi Wang; Hong Zhang; Liling Dai; Tongguo Song; Ping Li; Yali Liu; Luning Wang (Cell Biochemistry and Biophysics, 2015)

Identification of fungal genes involved in the preinfection events between ectomycorrhizal association (Pisolithus tinctorius and Pinus massoniana) - Haibo Li; Huazheng Peng; Liling Wang; Hailong Wei; Nan Li; Qunying Jing (Mycological Progress, 2014)

Boletus roseoflavus, a new species of Boletus in section Appendiculati from China - Haibo Li; Hailong Wei; Huazheng Peng; Hongmei Ding; Liling Wang; Liang He; Lizhong Fu (Mycological Progress, 2014)

Photocatalytic degradation of phenol with mesoporous TiO2−xBx - Leyan Xiong; Longzhen Zheng; Jingpeng Xu; Dan Zheng; Junhua Li; Xinjia Li; Juan Sun; Qiang Liu; Liling Niu; Shaoming Yang; Jian Xia (Environmental Chemistry Letters, 2011)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)